Göring’s man in Paris : the story of a Nazi art plunderer and his world - Petropoulos, Jonathan (Yale University Press, 2021)
Frontmatter -- Contents -- Dramatis Personae -- Prologue: Kaffee und Kuchen with Bruno -- Introduction -- 1. Art Historian, Art Dealer, Member of the SS (1911–41) -- 2. The “King of Paris” (1941–43) -- 3. Darker Hues and War’s End (1943–45) -- 4. Called to Account (1945–50) -- 5. The Amnesia Years -- 6. Lohse in North America -- 7. War Stories, War Secrets -- 8. Restitution -- 9. Bruno Lohse and the Wildensteins -- Epilogue: On the Trail of the Nazi Plunderers -- Appendix: Artworks in the Possession of Dr. Bruno Lohse and the Schönart Anstalt -- Acknowledgments -- List of Abbreviations -- Notes -- Prologue -- Index